Draft Genome Sequence of Propionispora sp. Strain 2/2-37, a New Xylan-Degrading Bacterium Isolated from a Mesophilic Biogas Reactor - Koeck, Daniela E. (Genome Announc, 2016)
The novel mesophilic bacterial strain Propionispora sp. 2/2-37 was isolated from an industrial-scale biogas plant. Comparative 16S rRNA gene sequencing revealed that the isolate constitutes a new subcluster within the order Selenomonadales. The 2/2-37 draft genome sequence was established and provides the genetic basis for application of this microorganism in degradation of biomass for bio-fuel production.